Field measurements of a massive Porites coral at Goolboodi (Orpheus Island), Great Barrier Reef - Smith A; Cook N; Cook K; Brown R; Woodgett R; Veron J; Saylor V (Springer Nature Limited, 2021)
An exceptionally large coral Porites sp. has been identified and measured at Goolboodi (Orpheus Island), Great Barrier Reef (GBR). This coral was measured in March 2021 during citizen science research of coral reefs in the Palm Islands group. We conducted a literature review and consulted scientists to compare the size, age and health of the Porites with others in the GBR and internationally. This is the largest diameter Porites coral measured by scientists and the sixth highest coral measured in the GBR. The health of the Porites was assessed as very good with over 70% live coral cover and minor percentages of sponge, live coral rock and macroalgae. An estimated age of 421-438 years was calculated based on linear growth models. Manbarra Traditional Owners were consulted and suggested that the Porites be named Muga dhambi (big coral) to communicate traditional knowledge, language and culture to indigenous, tourists, scientists and students.
Keywords: Ecology; Environmental sciences; Ocean sciences; Zoology